Dosis de ácido-3-Indol butírico en el enraizamiento de estacas de Sacha Inchi (plukenetia volubilis l.) en diferentes Sustratos - Bartra Ramírez, Javier (2009)
An alternative to meet the market demand with sacha inchi is the establishment of plantations with select product characteristics to achieve higher genetic gains in the shortest possible time increasing the quality and productivity of the plantations, however is a problem of breakdown of seed of genetic quality and quantity for the oil industry, this makes the vegetative propagation acquires great importance. The objective was to assess environmental conditions (relative humidity, air temperature, substrate temperature and solar radiation) and the rooting of cuttings of basal sacha inchi (Plukenetia volubilis), under the effect of two types of substrates (sand and half fine gravel) and four doses of acid-3-indole butyric acid (0.1%, 0.2%, 0.4%, 0.8%), using propagators sub irrigation. The research was conducted at the experimental nursery of the Research Institute of the Peruvian Amazon (IIAP), San Martín, using a split plot design in randomized complete block with four replicates and twelve cuttings per experimental unit. At the end of the trial (after 30 days in the propagator), rooting percentages were obtained on substrates of sand averaged 65.83% and 62.50% of fine gravel. The best rooting percentage was achieved with a sand substrate with half dose of AIB andalusia 0.2%, in general, the species can be easily rooted in sand, using shadows to permit the passage of 20% of light, thus achieving optimal average irradiation (74.46 lux), relative humidity (77.86%) air temperatures (27.66 ° C) and substrate (27.84 ° C) in the propag ators. Keywords: Plukenetia volubilis, vegetative propagation, rooting, juvenile stakes, pole length, leaf area, sub chamber irrigation.